2009
DOI: 10.1136/hrt.2009.173153
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity-related differences in left ventricular function, structure and geometry: a population study of UK Indian Asian and European white subjects

Abstract: Compared to European white people, Indian Asians had attenuated longitudinal LV function, higher LV filling pressure and demonstrated a greater degree of concentric remodelling independent of other demographic and clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 44 publications
6
72
1
1
Order By: Relevance
“…Such mechanisms involved, were probably due to increased sympathetic activity (norepinephrine release) and involvement of rennin-angiotensin-aldosterone system [25]. Balci et al, [30] observed the similar results related to systolic function in essential hypertension.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Such mechanisms involved, were probably due to increased sympathetic activity (norepinephrine release) and involvement of rennin-angiotensin-aldosterone system [25]. Balci et al, [30] observed the similar results related to systolic function in essential hypertension.…”
Section: Discussionmentioning
confidence: 68%
“…an increased HR, SV, CO, and CI, including TPR [25]. In hypertension, reduced CO is mainly the result of LV diastolic dysfunction in the course of LVH and decreased beta-receptor reactivity in the mode of "down-regulation".…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CHD, heart attack or angina, diabetes and hypertension were established on the basis of questionnaire self-report of a doctor's diagnosis. As these conditions had been tested for in LOLIPOP [10], including ECG, blood pressure and fasting blood glucose measurements, it is likely that much previously undiagnosed disease had already been detected, reducing the chance of inter-ethnic biases in detection rates. Ethnicity was confirmed with the participant, based on selfassessment and place of birth of all four grandparents.…”
Section: Methodsmentioning
confidence: 99%
“…Study of clinic populations, or studies excluding individuals on the basis of treatments or disease may result in a sample that is biased by ethnicity (as clinic attendance, disease and treatment vary markedly by ethnicity), making the findings uninterpretable. We therefore recruited from the London Life Science Prospective Population Study (LOLIPOP), a West London multi-ethnic, population-based study of more than 25,000 individuals investigating chronic disease and its determinants [10]. Men (aged 35-75 years) and women (aged 55-75 years) were recruited to LOLIPOP from 58 primary care lists.…”
Section: Methodsmentioning
confidence: 99%
“…an increased heart rate( HR),stroke volume( SV),cardiac output(CO), and including Total Peripheral Resistant( TPR) 11 .…”
Section: Discussionmentioning
confidence: 99%